Analisis Pengambilan Keputusan Investasi Menggunakan Metode Discounted Cash Flow pada Saham Sub Sektor Perbankan Syariah - Sari, Widya (Masoem University, 2024)
The financial sector, especially the banking subsector, has a market capitalization value ranked in the top 10 on the Indonesian Stock Exchange. Investors do not only rely on existing phenomena, but in deciding to invest they need to carry out stock analysis using a basic approach that can reduce losses and increase profits. This research aims to make investors know how to apply the best techniques in predicting stock prices for the next five years. The fundamental analysis used is the Discounted Cash Flow (DCF) method with the Free Cash Flow to Firm (FCFF) approach. This research is descriptive research with a quantitative approach without testing hypotheses. The pusposive sampling method was used in this research to select 2 sharia banks that met the criteria in accordance with this research which had the stock code BTPS (Bank BTPN Syariah) and PNBS (Bank Panin Dubai Syariah). By assessing share price valuation, the results obtained in this research are that BTPS and PNBS shares are in the undervalued category, the best investment decision that investors can choose is to buy them. However, to obtain optimal results it needs to be combined with other analyzes, namely technical analysis and money management.